Properties of residuals for spatial point processes - Baddeley, Adrian; Møller, J.; Pakes, A. (Kluwer Academic Publishers, 2008)
For any point process in Rd that has a Papangelou conditional intensity ?, we define a random measure of 'innovations' which has mean zero. When the point process model parameters are estimated from data, there is an analogous random measure of 'residuals'. We analyse properties of the innovations and residuals, including first and second moments, conditional independence, a martingale property, and lack of correlation. Some large sample asymptotics are studied. We derive the marginal distribution of smoothed residuals by solving a distributional equivalence. © 2007 The Institute of Statistical Mathematics.